Design and execution of building investments using BIM technology for facilities subject to the polish military administration - Wójtowicz, Maciej (AIP conference proceedings, 2019)
BIM technology is now a very widely discussed and commented area. However, it is still not commonly used in construction investments. Budgetary entities within the Polish public finance sector are beginning to be interested in its application, and more and more often require the use of this standard by designers and contractors. The paper covers issues related to the implementation of BIM technology in Poland on the example of military facilities and military investments. Along with the application of BIM, consideration must be given to the advantages, difficulties and potential risks which are associated with it. The analysis also covers the profitability of introducing BIM in Poland in the context of current project standards and legal conditions. This is due to the fact that the adaptation of public investments to this type of methodology is spread over time, and requires awareness and cooperation of all participants in the construction process.